Estudo comparativo da atualização da NBR 5419/2005 para a NBR 5419/2015 e aplicação prática para canteiro de obras em área de mineração - SANTOS, Letícia Leão dos (2022)
This paper is based on the current national standard for protection against atmospheric discharges (ABNT NBR 5419:2015), making an analysis of the changes that have occurred since its previous version published in 2005. Finally, it demonstrates a practical application in a construction site located in an area of mining activity. Elaborating an SPDA that meets the current standards, as well as the demands requested for the site and its physical characteristics. Of all the changes that occurred between the two versions of NBR 5419, the one with the greatest impact on the elaboration of an SPDA project is the risk analysis, including new parameters to be considered in order to determine the risks of a hazardous event. In order to make this analysis more practical and less exhaustive regarding the calculations, an Excel spreadsheet will be used as a tool to perform the calculations. This tool considers all the values and parameters as provided by NBR 5419. This way it will be possible to verify if the project is effectively able to protect the structure from a possible lightning discharge. The final chapter of this work contains the SPDA project that was developed and implemented for this construction site.